1996
DOI: 10.1016/s0969-2126(96)00091-3
|View full text |Cite
|
Sign up to set email alerts
|

Structure of unliganded HIV-1 reverse transcriptase at 2.7 å resolution: implications of conformational changes for polymerization and inhibition mechanisms

Abstract: The p66 thumb subdomain is extremely flexible. NNRTI binding induces both short-range and long-range structural distortions in several domains of RT, which are expected to alter the position and conformation of the template-primer. These changes may account for the inhibition of polymerization and the alteration of the cleavage specificity of RNase H by NNRTI binding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
346
0
6

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(365 citation statements)
references
References 27 publications
13
346
0
6
Order By: Relevance
“…analysed here, as well as by structures from other laboratories [where the p66 thumb has been observed to be folded down against the rest of the molecule (Rodgers et al, 1995;Hsiou et al, 1996)]. We conclude that (especially for the p66 thumb) crystal packing is the major factor determining the orientation of these domains, at least within the range we observe.…”
Section: Discussionsupporting
confidence: 75%
“…analysed here, as well as by structures from other laboratories [where the p66 thumb has been observed to be folded down against the rest of the molecule (Rodgers et al, 1995;Hsiou et al, 1996)]. We conclude that (especially for the p66 thumb) crystal packing is the major factor determining the orientation of these domains, at least within the range we observe.…”
Section: Discussionsupporting
confidence: 75%
“…4b) from the position that it occupies in DNA-bound HIV-1 RT complexes (51)(52)(53)(54)(55) and in unliganded HIV-1 RT structures crystallized in the absence of inhibitors (21,22,24). In other NNRTI complexes with HIV-1 RT, the displacement of Trp-229 is required for the rearrangements of Tyr-181 and Tyr-188 that occur upon inhibitor binding.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent structures of the enzyme with a number of different NNRTIs bound have demonstrated that these inhibitors bind to the same pocket, with only minor differences in protein conformation, and substantially overlap the site occupied by nevirapine (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Comparison of these structures with those of the apoenzyme shows that the NNRTI-binding pocket is induced upon NNRTI binding (21)(22)(23)(24).…”
mentioning
confidence: 99%
“…In nucleic acid-containing crystal structures, catalytic aspartates are close to the 3Ј terminus of the primer. Asp-185 and Asp-186 are part of the conserved -TyrMet-Asp-Asp-motif, which adopts an unusual ␤-turn conformation (29,35,48), possibly to promote their positioning for catalysis, whereas the Tyr-183 phenoxy side chain is involved in hydrogen bonding with nucleobases at position Ϫ2 (29). Comparison of the crystal structures of DNA-bound RT with unliganded or non-nucleoside RT inhibitor (NNRTI)-bound enzymes reveals significant conformational differences for the -Tyr-Met-Asp-Asp-motif, implicating a high degree of structural flexibility (29).…”
mentioning
confidence: 99%